Cytotoxicity of Gambir Leaf Infusion (Uncaria gambir Roxb.) on T47D Cells: In Vitro Assay - Fadholly, Amaq (Jurnal Veteriner dan Biomedis, 2025)
Cancer is a cellular pathology marked by the disruption of regulatory mechanisms governing the cell cycle and homeostasis in multicellular organisms. This study seeks to evaluate the cytotoxic effects and IC50 value of Uncina gambir leaf infusion on the T47D cell line, utilized as a model for mammary cancer. The cytotoxic activity of Uncina gambir leaf extract  was assessed by delivering five concentrations of the test substance: 10 μg/ml, 20 μg/ml, 40 μg/ml, and 80 μg/ml to T47D cell lines, followed by a 24-hour incubation period. Cell counting was conducted following the administration of MTT and SDS stop solution. The inhibition percentages for each test sample concentration were 25.11%, 33.76%, 43.79%, and 48.09%, respectively. The extract of Uncina gambir leaf infusion exhibits an IC50 value of 502.12 μg/mL. The IC50 value of Uncina gambir leaf infusion against T47D cell lines acts as non toxic for the cytotoxicity group. Consequently, it may be inferred that Uncina gambir leaf extract exhibits no cytotoxicity towards T47D cell lines.